Merajut Keberagaman: Tantangan dan Peluang dalam Pengelolaan Festival Budaya untuk Membangun Kohesi Sosial dan Pariwisata Berkelanjutan - lasaiba, Mohammad Amin (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2021)
This study explores the significant role of festivals and cultural celebrations in promoting cultural diversity and supporting tourism. Cultural festivals serve as strategic tools for attracting tourists, boosting local economic revenue, and strengthening the cultural identity of communities. This research employs a literature review method to analyze the various impacts of festivals, including financial, social, and cultural benefits and the challenges faced in festival management. The analysis results indicate that while cultural festivals can strengthen social cohesion and promote intercultural understanding, their success heavily depends on effective planning, inclusive management, and active involvement of the local community. Security issues, community participation, and environmental impact must be addressed holistically to ensure maximum benefits. With proper management, cultural festivals reflect a rich cultural heritage essential to sustainable and inclusive tourism development. Therefore, cultural festivals have significant potential to support global tourism development, provided the management strategies are adaptive to the evolving needs and challenges